Role of Knowledge Sharing and Employee Engagement Towards Innovative Performance with Learning Orientation as Moderating Variable - Alfian Nur Satrio Ajie; Marno Nugroho (Jurnal Maksipreneur, 2023)
In this study, the authors will analyze the performance of innovation through knowledge sharing, and employee work involvement moderated by learning orientation variables. The purpose of this study is to determine the extent to which innovation performance can be obtained through knowledge sharing, work involvement, and moderation of learning orientation that develops in the process of holding state-owned companies in the banking sector. One of them is the existence of an interesting holding process between PT Bank Rakyat Indonesia, Tbk. (Bank BRI), PT Permodalan Nasional Madani (PNM), and PT Pegadaian, where PT Pegadaian can be considered a non-banking sector service. Thus, knowledge sharing and employee involvement, in this case, will be analyzed using learning orientation as a moderating variable. This type of research is explanatory research with a cross-sectional design and data collection using primary data in the form of data collection questionnaires distributed to employees of Bank BRI. The sample of this research is 213 respondents and will be analyzed using SEM-PLS 3.0. The results of this study indicate that knowledge sharing has a significant effect on innovation performance, employee involvement has a significant effect on innovation performance, and the results of learning orientation are able to significantly moderate knowledge sharing on innovation performance. However, learning orientation cannot moderate and is not significant between employee engagement and innovation performance.